Institutional logics and organisational hybridity: English housing associations' diversification into the private rented sector. Issue 8 (16th November 2016) - Morrison, Nicky
Abstract: State withdrawal combined with challenges in raising private finance has led not-for-profit housing organisations in a range of countries to diversify into commercial activities as means to generate additional income streams and cross subsidise their core social operations. Within England, an increasing number of housing associations (HAs) has looked for new forms of investment, notably from private rental housing, to generate additional cash flows and fill gaps in the housing market. Drawing on the concepts of institutional logics and organisational hybridity, the paper uses organisational archetypes to examine the different hybrid financing, governance structures and housing products that two pioneering London-based HAs have employed to undertake private rental activities alongside their social businesses. The paper argues that the trends identified are indicative of wider institutional change, with not-for-profit housing organisations facing difficult strategic choices about how to fund their core business in a world of lower public subsidy and uncertainty over future sources of private finance.